Unilateral cleft lip surgery symmetry observation with Millard I and Tennison techniques - Salsabila, Rizentya; Kresnaputri, Dewi Rarasati; Sieman, Riani; Anugraha, Ganendra (Indonesian Journal of Dental Medicine, 2024)
Background: In line with the development of Millard I and Tennison cleft lip surgery techniques, there are also advantages and disadvantages to each technique. The Cleft Lip Symmetry Index (CLCSI) was used to measure the symmetry of each measurement variable from the results of unilateral cleft lip surgery so that it could be represented by an objective number. Purpose: This study aims to observe the surgery results using Millard I and Tennison techniques in unilateral cleft lip patients. Methods: This study used descriptive study by observing the symmetry of lateral philtrum height, vermillion height, cupid’s bow width, cupid’s bow height, and nostril width after labioplasty using the Millard and Tennison technique in unilateral cleft lip patients in Surabaya, Madura, and Malang. Results: The results of the CLCSI modification for the Millard technique can be summarized that nostril width ranged from 78.82 - 195.04. Lateral philtrum height ranged from 62.5 - 107.62. Cupid’s bow width ranged from 72.17 - 155.29. Cupid’s bow height ranged from 96.43 - 487.5. Vermilion height ranged from 84.62 - 131.11. The results of the CLCSI modification for the Tennison technique can be summarized that nostril width ranged from 88.89 - 171.43. Lateral philtrum height ranged from 48.92 - 109.04. Cupid’s bow width ranged from 89.26 - 166.15. Cupid’s bow height ranged from 73.81 - 311.11. Vermilion height ranged from 72.14 - 138.46. Conclusion: It’s difficult to obtain completely symmetrical surgical results because of many factors that affect the outcome of the operation in both Millard I and Tennison methods.